Análisis de las cargas no lineales y su incidencia en la generación de armónicos de la nave de soldadura de la empresa Ciauto cía. ltda. en el 2022 - Pérez López, Jaime Efraín (2023)
This project focused on a comprehensive analysis of non-linear loads and their influence on the generation of harmonics in a welding hall belonging to the company CIAUTO Cía. Ltda. A detailed study was made of the presence of harmonics in an electrical network and their potential to cause a series of adverse problems, such as vibrations in electrical machines, overload in phases and neutral conductors, and tripping of main breakers. To determine the most significant harmonics, the Fluke analyzer was used to perform a more accurate analysis, the third, fifth, and seventh harmonic being the most representative. Ultimately, a comprehensive analysis was carried out for the implementation of specific corrections to mitigate the previous harmonics using passive filters. These filters were very effective in reducing the level of harmonics in the welding hall, minimizing them by up to 81%, as in the case of the seventh harmonic. This intervention has led to a significant improvement in the performance and efficiency of the electrical system in the welding hall, avoiding problems related to the presence of harmonics and their adverse effects on the electrical equipment.